Pendampingan Pengembangan Teknologi Berbasis Digital Sebagai Bentuk Tersedianya Bank Soal di Pondok Pesantren Nurul Qur’an Ponorogo - Yoga Nur Setiawan; Dewi Yunita Sari (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The aim of study is to develop digital technology that can be used to provide question banks at the Nurul Qur’an Islamic boarding Scholl in Ponorogo. The Backgrounds of this reserch is need for an effective yet efficient and systematic learning evaluation system, considering that manual question creation often takes a long time and can lead to discrepancies in standars. The method applied in this reserch is the ABCD (Asset- Based Community Development). This approach focuses on utilizing the assets and potentials owned by the Pesantren or Nurul Qur’an Islamic Boarding Scholl, both in terms of human resources, Infrastrukture, and community support, as the basis for designing educational innovations. The reserch process includes indentifying available assets, building collaboration among pesantren parties, developing a digital- based questions bank system, and implementing and strengthening the sustainability of the program, and implementing this program collaboration the method applied this research ADDIE (Analysis, Design, Development, Implementation, Evaluation) Development model which includes steps to analyze needs, design the system, develop this application, implement it in the boarding school environtment, and evaluate iit effectiveness. The result of the study indicate that the use of digitally-based question banks can assist teachers un organizing questions, improving the quality of learning evaluations, and providing faster and more organized access for student and educators. Therefore, the development of this digital technology is expected to be an innovative solution to support the modernization of the education system in Islamic boarding schools without eliminating the existing traditional values.